Representation and Regulation: Understanding Foods Served in Wayang Kulit Performances in Malang and Jombang - Rasyid Fahmi Suroso; Adi Dwi Riyanto; Nadya Afdholy (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
This study investigates foods served in wayang kulit performances in Malang and Jombang, employing the circuit of culture perspective as a methodological framework. It delivers an overview of the representation and regulation of foods served in wayang kulit performances. Data collection techniques consist of observation, documentation, and semi-structured interviews with two dalangs (shadow puppet masters), one in Bareng, Jombang, and the other in Blimbing, Malang. By analyzing foods served in wayang kulit performances in the circuit of culture, this study aims to provide more interpretations of the situation.